Mistakes and complications in treating broad feet with a valgus deviation of the great toe - Prozorovsky, Dmytro; Romanenko, Konstantin; Bitsadze, Marianna (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2010)
The article describes the typical mistakes, which are made in treating patients with a spread anterior part of the foot combined with a valgus deformity of the great toe. Attention is focused on such complications as a relapse of the deformity, a jatrogenic varus deformity of the great toe, some rigidness of the great toe, the presence of plantar callosities. The following mistakes were analysed: performance of palliative surgical interventions, underestimation of the angulation of the articular surface of the first metatarsal bone head, technical failures during corrective osteotomies, mistakes during McBride procedure, and shortcomings at the postoperative period